Lung Inflation With Hydrogen During the Cold Ischemia Phase Alleviates Lung Ischemia-Reperfusion Injury by Inhibiting Pyroptosis in Rats - Zheng, Panpan; Kang, Jiyu; Xing, Entong; Zheng, Bin; Wang, Xueyao; Zhou, Huacheng (Frontiers in Physiology, 2021)
Background Lung inflation with hydrogen is an effective method to protect donor lungs from lung ischemia-reperfusion injury (IRI). This study aimed to examine the effect of lung inflation with 3% hydrogen during the cold ischemia phase on pyroptosis in lung grafts in rats. Methods Adult male Wistar rats were randomly divided into the sham group, the control group, the oxygen (O2) group, and the hydrogen (H2) group. The sham group underwent thoracotomy but no lung transplantation. In the control group, the donor lungs were deflated for 2 h. In the O2 and H2 groups, the donor lungs were inflated with 40% O2 + 60% N2 and 3% H2 + 40% O2 + 57% N2, respectively, at 10 mL/kg, and the gas was replaced every 20 min during the cold ischemia phase for 2 h. Two hours after orthotopic lung transplantation, the recipients were euthanized. Results Compared with the control group, the O2 and H2 groups improved oxygenation indices, decreases the inflammatory response and oxidative stress, reduced lung injury, and improved P-V curves. H2 had a better therapeutic effect than O2. Furthermore, the levels of the pyroptosis-related proteins NLRP3, caspase-1 p20, and GSDMD-N were decreased in the H2 group. Conclusion: Lung inflation with 3% hydrogen during the cold ischemia phase inhibited the inflammatory response, oxidative stress, and pyroptosis and improved the function of the graft. Inhibiting ROS production may be the main mechanism of the antipyroptotic effect of hydrogen.